2016 IEEE-RAS 16th International Conference on Humanoid Robots (Humanoids) 2016
DOI: 10.1109/humanoids.2016.7803357
|View full text |Cite
|
Sign up to set email alerts
|

Robot gains social intelligence through multimodal deep reinforcement learning

Abstract: For robots to coexist with humans in a social world like ours, it is crucial that they possess human-like social interaction skills. Programming a robot to possess such skills is a challenging task. In this paper, we propose a Multimodal Deep Q-Network (MDQN) to enable a robot to learn human-like interaction skills through a trial and error method. This paper aims to develop a robot that gathers data during its interaction with a human, and learns human interaction behavior from the high dimensional sensory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 16 publications
0
80
0
19
Order By: Relevance
“…However, we want to move away from feature engineering and formulate our human-robot interaction scenario as a deep reinforcement learning problem. Recent studies in HRI showed impressive results in employing deep reinforcement learning for various applications [14,15,12]. The main challenge for deep learning approaches is the lack of training data from human studies but we plan to tackle this problem using our current Bayesian-based model to simulate human behaviour data as a prior for the deep reinforcement learning model.…”
Section: Resultsmentioning
confidence: 99%
“…However, we want to move away from feature engineering and formulate our human-robot interaction scenario as a deep reinforcement learning problem. Recent studies in HRI showed impressive results in employing deep reinforcement learning for various applications [14,15,12]. The main challenge for deep learning approaches is the lack of training data from human studies but we plan to tackle this problem using our current Bayesian-based model to simulate human behaviour data as a prior for the deep reinforcement learning model.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally, the same trend can be observed regarding the problem of adaptation in HRI. One of the pioneer works was conducted by Qureshi in 2017 [29] where a Deep Q-Network [27] was used to learn a mapping from visual input to one of the several predefined actions for greeting people.…”
Section: Related Workmentioning
confidence: 99%
“…Several works have shown its use in training of an agent for behaviors similar to that of humans. The works by Qureshi et al [12] [13] presented an RL method for training an agent to greet as humans with the sequential actions of wait, look, wave and shake hand. They used multi-modal DQN and generated rewards at every successful handshake.…”
Section: Social Robots and Rlmentioning
confidence: 99%